Invasif dan Persisten Pasteurella multocida Setelah Diinokulasi Secara Intratracheal pada Kalkun - Abrar, Mahdi; Fakhrurrazi, Fakhrurrazi (Jurnal Kedokteran Hewan, 2010)
The objective of this study was to evaluate the invasiveness and persistence of Pasteurella multocida after intratracheal inoculation on turkeys. Four strains of Pasteurella multocida, P-1059, T-325, CU, and M-9 were used in this study and intratracheally (IT) inoculated into turkeys. The number of viable bacteria in the trachea, lung, liver, spleen, and the blood were enumerated during periods of 6 and 9 hrs post inoculation (PI). The result showed that four strains of organism were present in the organ and the tissues observed. In the liver, spleen, and blood, the virulent P-1059 strain showed significant increases within 6 or 9 hrs PI. Strain CU showed significant increase only in the spleen. Two other strains did not show significant increase in any organs; strain M-9, on the other hand, showed significant decrease in the trachea. These results indicated that P-1059 and three other strains showed their ability to invade the tissues or organs when they are intratracheally inoculated.